Localized triatomic self-assembly : unveiling long-range chemical anisotropy in exfoliated black phosphorus - Pokle, Anuj S. (Trinity College (Dublin, Ireland). School of Physics, 2017)
With the emergence of the two dimensional (2D) materials, the feasibility of mass-scale production has been proven by performing Liquid Phase Exfoliation (LPE), Chemical Vapour Deposition (CVD), Plasma Laser Deposition (PLD), Molecular Beam Epitaxy (MBE), etc. Proving to be excellent in the device, optical, battery and various other applications, the main challenge is to characterise these materials. Scanning/ Transmission Electron Microscopy (S/TEM) has proven to be a very powerful technique which simultaneously allows you to investigate the structure and its local physicalchemical properties (using Electron Energy Loss Spectroscopy - EELS) at the atomic scale. With the current development in the field of electron microscopy, in-situ experiments have changed the way we used to think about the material response towards electrical, strain, heat etc. This thesis is devoted to the study of 2D material especially Black Phosphorous (BP) or also referred to as Phosphorene. BP was synthesised (bulk form) hundred years ago, but it is just recently in 2014 that it was reintroduced from a perspective of a layered thin film material. Many previously unidentified properties have arisen which attracted tremendous interest from material scientists, semiconductor industry, chemists to condensed matter physicists.
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2017